(untitled) - Matthiesen, Steven J. (New York, 2014)
Approximately 500 words and their definitions are presented here for ESL students preparing to take the TOEFL. The book also presents detailed advice on ways that students can expand their English language vocabulary.--Publisher's description.
Keywords: Tiếng Anh,Kiểm tra tiếng Anh như một ngoại ngữ,Tiếng Anh,Test of English as a Foreign Language,English language,English language,Vocabulary,Vocabulary,Vocabulary,Vocabulary,Từ vựng; Kỳ thi,Examinations,Examinations,Examinations,Examinations,Examinations,Kỳ thi